2020
DOI: 10.7759/cureus.9038
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Therapy With Corticosteroids and Intravenous Immunoglobulin in the Management of Severe Tocilizumab-Resistant COVID-19: A Report of Three Clinical Cases

Abstract: We present the cases of three patients with severe, life-threatening coronavirus disease 2019 (COVID-19) who had failed to achieve substantial improvement on intial treatment. They subsequently received pulse therapy with methylprednisolone [1,000 mg/day intravenously (IV) for three consecutive days] and IV immunoglobulin (20 g/day). This treatment regimen was associated with a prompt resolution of respiratory failure, elimination of clinical manifestations of the cytokine release syndrome (CRS), and reversal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Two case studies reported favourable responses of COVID-19 patients to the other powerful synthetic glucocorticoid methylprednisolone: a case of a renal transplant recipient [ 70 ] and three severe cases who did not respond to therapy with the IL-6 inhibitor tocilizumab [ 71 ]. The latter three cases showed a rapid improvement with pulse administration of a high daily intravenous dose of methylprednisolone of 1 g for 3 days and intravenous immunoglobulin.…”
Section: Potential Therapies Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Two case studies reported favourable responses of COVID-19 patients to the other powerful synthetic glucocorticoid methylprednisolone: a case of a renal transplant recipient [ 70 ] and three severe cases who did not respond to therapy with the IL-6 inhibitor tocilizumab [ 71 ]. The latter three cases showed a rapid improvement with pulse administration of a high daily intravenous dose of methylprednisolone of 1 g for 3 days and intravenous immunoglobulin.…”
Section: Potential Therapies Of Covid-19mentioning
confidence: 99%
“…A number of IL-6 antagonists are also being trialled, including tocilizumab [ 71 , 74 , 75 ]. Small numbers of patients were examined to draw firm conclusions [ 71 , 74 ] and, whereas it is effective in some patients and can reduce the risk of mechanical ventilation and death, this drug can also induce new infections [ 75 ]. Inhibition of angiotensin-converting enzyme, ACE 2, has also been suggested.…”
Section: Potential Therapies Of Covid-19mentioning
confidence: 99%
“…Cao et al reported on 3 severe patients with COVID-19 who received high-dose IVIg with satisfactory recovery [8] . Sheianov et al presented the cases of three severe patients with COVID-19 who had failed to achieve substantial improvement on intial treatment [16] . They subsequently received pulse therapy with methylprednisolone and IVIg (20 g/day), which was associated with a prompt resolution of respiratory failure, elimination of clinical manifestations, and reversal of pulmonary CT changes [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Sheianov et al presented the cases of three severe patients with COVID-19 who had failed to achieve substantial improvement on intial treatment [16] . They subsequently received pulse therapy with methylprednisolone and IVIg (20 g/day), which was associated with a prompt resolution of respiratory failure, elimination of clinical manifestations, and reversal of pulmonary CT changes [16] . However, confounding factors of the two studies include the lack of case-matched control patients.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the potential of hematological biomarkers, WBC counts are subject to change due to simultaneous viral or bacterial infections [ 168 ]. Steroids (like glucocorticoids) and intravenous immunoglobulin therapy can also alter WBC counts [ 168 ], both of which have been considered for COVID-19 treatment [ 169 ] [ 170 ].…”
Section: Biological Markers Of Inflammationmentioning
confidence: 99%